Penerapan Metode Asosiatif Untuk Menganalisis Pengaruh Penetapan Harga dan Promosi Terhadap Kepuasan Penggunaan Provider - Suhairi, Suhairi; Aris Kukuh Prasetyo; Wulandari, Ayu; Simbolon, Rizki Anggiani (JDMIS: Journal of Data Mining and Information Systems, 2023)
Provider cards definitely have their advantages and disadvantages in the hearts of their users. In every advantage, there must be an effort by business people to maintain it as a product advantage. Then behind the deficiencies, there must also be an extra effort made by businesses to minimize it so that it doesn't become a reason for consumers to switch to other providers. In addition, there are also other efforts made by business providers in terms of competition, such as in the field of pricing and promotion. The right step in setting prices and also choosing a way of promotion will bring entrepreneurs the only choice in the hearts of consumers. Pricing according to quality as well as attractive promotions will usually be able to be the most important thing in business competition. This research will use a qualitative method with an associative method with a population of UINSU students and a sample of 100 students. The final results show which provider is able to win the hearts of consumers and become the most chosen by the provider card users that have been presented by researchers, namely Indosat providers.